2018
DOI: 10.1071/aj17152
|View full text |Cite
|
Sign up to set email alerts
|

Social media use in the Australian energy and resources sectors

Abstract: Abstract. Social media is becoming ubiquitous, but may not always be an effective way for companies to interact with their stakeholders. This paper reports the results of ongoing assessments of social media use in the Australian energy and resource sectors, starting from 2013. Nearly all energy and mining companies had publicly accessible websites but, while increasing, social media use is (still) relatively limited compared to other industries. LinkedIn (with a recruitment focus) was the social media channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In fact, many firms operate more than one social media channel to enhance their online presence and social media leadership. These findings are consistent with those of Styan (2018), who found that operating more than one social media channel is beneficial for corporations in the energy and resources market, as it enables them to reach specific communities that prefer a particular social media channel, such as LinkedIn for networking professionals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, many firms operate more than one social media channel to enhance their online presence and social media leadership. These findings are consistent with those of Styan (2018), who found that operating more than one social media channel is beneficial for corporations in the energy and resources market, as it enables them to reach specific communities that prefer a particular social media channel, such as LinkedIn for networking professionals.…”
Section: Discussionsupporting
confidence: 90%
“…The growing preference for social media use by the corporate sector is largely informed by its effectiveness in engaging the key stakeholders of the company, including customers, owners, the business community, and the media, with firms taking advantage of the interactive features of such platforms to exchange ideas, collect feedback, and respond to concerns raised about the company's brand, products, or services (Styan, 2018). Most firms operating in the energy and resources sector try to maintain a strong social media presence on their preferred social media platform, in addition to operating an official corporate website (Styan et al, 2015). The acceptance of external knowledge on social media by energy and resources companies can also promote the change of companies (Saura et al, 2023).…”
Section: Social Media Usage In the Energy And Resources Sectormentioning
confidence: 99%
“…While the main points of the exercises are to get the students to consider whether and how social media can be used for communicating with stakeholders, a sizeable database on social media use in the energy and resources sectors has been generated -providing a unique benchmark for industry to consider, which has been motivating for students to be involved in. Subsequently, several students have volunteered to work in partnership with the module coordinator after the course to work up the data into a full written paper, some of which was presented at an international conference on Social Responsibility in Mining in late 2015 (Styan et al 2015). Students value the opportunity to engage in research, work in partnership with an academic member of staff, and produce assessments aimed at audiences which include industry sectors that students are interested in joining.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several students have volunteered to work in partnership with the module coordinator after the course to work up the data into a full written paper, some of which was presented at an international conference on Social Responsibility in Mining in late 2015 (Styan et al 2015). Students value the opportunity to engage in research, work in partnership with an academic member of staff, and produce assessments aimed at audiences which include industry sectors that students are interested in joining.…”
Section: Gwyneth Hughes Is Reader In Higher Education and A Connectedmentioning
confidence: 99%